306 HEART FAILURE AS THE CANCER FOR THE HEART: THE PROGNOSTIC ROLE OF THE HLM SCORE. (15th December 2022) - Severino, Paolo; Mancone, Massimo; D´amato, Andrea; Mariani, Marco Valerio; Prosperi, Silvia; Fegatelli, Danilo Alunni; Birtolo, Lucia Ilaria; Angotti, Danilo; Costi, Bettina; Cestiè, Claudia; Francia, Aurora Labbro; Tomarelli, Elisa; et al.
Abstract: Background: The multiorgan involvement of heart failure is similar to the spread observed in cancer. We proposed a new score, named HLM, analogous to TNM classification used in oncology. HLM refers to (i) H: heart damage, instead of "T" for tumor; (ii) L: lung involvement, instead of "N" for lymph nodes; (iii) M: systemic multiorgan involvement, instead of "M" for metastasis. Objectives: to compare HLM score to NYHA class, ACC/AHA stages and left ventricular ejection fraction (LVEF) classification, to assess the most accurate prognostic tool for HF patients. Methods: We performed a multicentric, observational, prospective study of consecutive patients admitted for HF, or at risk for HF. Parameters for heart, lungs and organs' function were collected. Each patient was classified according to HLM, NYHA, ACC/AHA stages and LVEF classification. Patients were followed up for 12 months. The primary composite endpoint was all-cause death and rehospitalization due to HF. Results: We enrolled 1720 patients who completed the 12-month follow-up. As shown by Kaplan Meier curves, HLM was the most accurate score to predict primary endpoint at 12- month. The area under the ROC curve (AUC) was greater for HLM score than NYHA, ACC/AHA stages and LVEF classification, regarding the composite endpoint (HLM=0.645; NYHA=0.580; ACC/AHA=0.589; LVEF=0.572) (Figure 1). HLM score related AUC showed statistically significant differences compared to LVEF (p=0.002), ACC/AHA (p=0.029) and NYHA (p=0.009). Conclusions: HLM score has a greater prognostic power compared to other nosologies, in terms of the composite endpoint of all-cause death and rehospitalization due to HF, at 12-month follow-up. Key words: heart failure; HLM score; prognosis; mortality; rehospitalization. Figure 1.